Leaf Biochemical and Physiological Responses to Elevated Atmospheric Ozone Concentration in Eight Modern Rice Cultivars - Longxin He; Mingxu Bao; Yi Li; Yansen Xu; Zaisheng Shao; Yanze Ma; Kun Zhang; Bo Shang; Zhaozhong Feng (Ecosystem Health and Sustainability)
This study investigated the effects of elevated O3 level on photosynthetic traits and antioxidant systems of various rice genotypes under fully open-air conditions. Eight modern rice cultivars (Oryza sativa L.), including 4 hybrids and 4 inbreds, were exposed to 2 O3 treatments: the ambient atmosphere (A-O3) and the 1.5 times ambient O3 concentration (E-O3) throughout the reproductive period. The measurements of gas exchange, chlorophyll a fluorescence, photosynthetic pigments, lipid oxidation, antioxidant content, and antioxidant enzyme activity were conducted on the flag leaf during the early and late grain-filling periods. The results indicated that E-O3 had differential effects on the photosynthesis and antioxidant indicators of rice genotypes. In the hybrid rice, the reduction in the light-saturated photosynthetic rate (Asat) was primarily due to the nonstomatal factors, such as the changes in antioxidants, particularly ascorbate and carotenoids. In contrast, the reduction in Asat levels in inbred rice was mainly due to the stomatal factors. Additionally, the hybrid rice was more sensitive to O3 than the inbred rice, with the sensitivity determinants varying between types. The sensitivity of hybrid rice to O3 was influenced by the magnitude of its antioxidant capacity, whereas the inbred rice sensitivity was determined by the stomatal conductance (gs) and the antioxidant enzyme activity. The rice cultivars with higher antioxidant enzyme activities could help mitigate the damage caused by O3 pollution. This study could provide valuable insights for screening the O3-tolerant rice cultivars and promoting the food security sustainability.